'The Hidden Victims'–Family Violence in Kinship Care in Victoria. (16th May 2018) - Breman, Rachel; MacRae, Ann; Vicary, Dave
Abstract : Family violence is endemic. It has a dramatic and negative impact upon the victims and the family systems in which it occurs. While there is a growing evidence base to support our understanding, prevention and treatment of family violence, little is known about some of its "hidden victims" (e.g., kinship carers). In 2017, Baptcare commenced research with 101 kinship carers in Victoria to gain a better understanding of how family violence, perpetrated by the child's close family member once the placement started, was impacting on children and families. In this context, family violence means any act of physical violence, emotional/psychological violence, verbal abuse and property damage. The study utilised a mixed design methodology that specifically targeted kinship carers who had direct experience of family violence. Findings from this study demonstrated that (1) many kinship carers, and the children in their care, experienced family violence early in the placement, (2) that the violence occurred frequently and (3) the incidents of violence did not occur in isolation. Carers sought support from multiple sources to deal with the family violence, however, the study illustrated that the usefulness of these supports varied. Additionally, findings highlighted reasons why many kinship carers felt reluctant to file a report to end the violence. The study described in this paper is the first step in understanding and exposing this multifaceted issue and delineates some of the major issues confronting Victorian kinship carers experiencing family violence – and the support required to ensure the safety of them and the children they care for. This paper will describe the approach that Baptcare is taking to address family violence in kinship care in western metropolitan Melbourne. This is the second paper in a three-part series relating to family violence in kinship care.